Salinity-Induced Changes in the Nutritional Quality of Bread Wheat (Triticum aestivum L.) Genotypes - Muhammad Nadeem; Muhammad Nouman Tariq; Muhammad Amjad; Muhammad Sajjad; Muhammad Akram; Muhammad Imran; Mohammad Ali Shariati; Tanweer Aslam Gondal; Nadezhda Kenijz; Dmitriy Kulikov (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
This research project was undertaken to study salinity stress changes in the nutritional quality of wheat genotypes. Four wheat genotypes SARC-1, SARC-5, SARC-7, and SARC-8 were grown under nonsaline and saline (7.5 dS/m and 15 dS/m) treatments. Salinity was created artificially by the addition of NaCl in soil before filling in pots. Recommended fertilizers N (120 kg/ha), P (100 kg/ha) and K (60 kg/ha) were used in the form of Urea, diammonium phosphate (DAP) and sulphate of potash (SOP) in both saline and non-saline treatments. The grains of wheat genotypes were evaluated for nutritional quality i.e. chemical composition, mineral contents, wet and dry gluten, gliadin and glutenin, and SDS-sedimentation value. The results showed that growth parameters (biological yield, number of grains, thousand grain weight, grain yield and grain length) were affected significantly by salinity stress. Protein contents were increased with salinity, whereas other parameters (moisture, ash, fat, fiber, glutenin, and SDS-Sedimentation value) were decreased by increasing salinity stress. Similarly, Na content increased while K, Ca, P, Fe, Mg and Zn decreased significantly by increasing salinity stress. Salinity stress affect positively on protein contents in grain of all wheat genotypes. SARC-7 and SARC-5 performed better than SARC-1 and SARC-8.